Effects of des-aspartate-angiotensin I on the actions of angiotensin III in the renal and mesenteric vasculature of normo-and hypertensive rats - Mustafa, M.R.; Dharmani, M.; N.K., K.; M. K., S. (Elsevier, 2004)
An earlier study showed that des-aspartate-angiotensin I (DAA-I) attenuated the pressor action of angiotensin III in aortic rings of the spontaneously hypertensive rat (SHR) but not the normotensive Wistar Kyoto (WKY) rat. The present study investigated similar properties of DAA-I in isolated perfused kidneys and mesenteric beds of WKY and SHR. In the renal vasculature, angiotensin III induced a dosedependent pressor response, which was more marked in the SHR than WKY in terms of significant greater magnitude of response and lower threshold. DAA-I attenuated the pressor action of angiotensin III in both the WKY and SHR. The attenuation in SHR was much more marked, occurring at doses as low as 10 15 M DAA-I, while effective attenuation was only seen with 10 9 M in WKY. The effects of DAA-I was not inhibited by PD123319 and indomethacin, indicating that its action was not mediated by angiotensin AT2 receptors and prostaglandins. However, the direct pressor action of angiotensin III in the SHR but not the WKY was attenuated by indomethacin suggesting that this notable difference could be due to known decreased response of renal vasculature to vasodilator prostaglandins in the SHR. Pressor responses to angiotensin III in the mesenteric vascular bed was also dose dependent, but smaller in magnitude compared to the renal response. The responses in the SHR, though generally smaller, were not significantly different from those of the WKY. This trend is in line with the similar observations with angiotensin III and II by other investigators. In terms of the effect of DAA-I, indomethacin and PD123319 on angiotensin III action, similar patterns to those of the renal vasculature were observed. This reaffirms that in the perfused kidney and mesenteric bed, where the majority of the vessels are contractile, femtomolar concentrations of DAA-I attenuates the pressor action of angiotensin III. The attenuation is not indomethacin sensitive and does not involve the angiotensin AT2 receptor. The findings suggest that DAA-I possesses protective vascular actions and is involved in the pathophysiology of hypertension.